Analysis of the Phenotypes in the Rett Networked Database - Elisa Frullanti; Filomena T. Papa; Elisa Grillo; Angus Clarke; Bruria Ben-Zeev; Mercedes Pineda; Nadia Bahi-Buisson; Thierry Bienvenu; Judith Armstrong; Ana Roche Martinez; Francesca Mari; Andreea Nissenkorn; et al. (International Journal of Genomics)
Rett spectrum disorder is a progressive neurological disease and the most common genetic cause of intellectual disability in females. MECP2 is the major causative gene. In addition, CDKL5 and FOXG1 mutations have been reported in Rett patients, especially with the atypical presentation. Each gene and different mutations within each gene contribute to variability in clinical presentation, and several groups worldwide performed genotype-phenotype correlation studies using cohorts of patients with classic and atypical forms of Rett spectrum disorder. The Rett Networked Database is a unified registry of clinical and molecular data of Rett patients, and it is currently one of the largest Rett registries worldwide with several hundred records provided by Rett expert clinicians from 13 countries. Collected data revealed that the majority of MECP2-mutated patients present with the classic form, the majority of CDKL5-mutated patients with the early-onset seizure variant, and the majority of FOXG1-mutated patients with the congenital form. A computation of severity scores further revealed significant differences between groups of patients and correlation with mutation types. The highly detailed phenotypic information contained in the Rett Networked Database allows the grouping of patients presenting specific clinical and genetic characteristics for studies by the Rett community and beyond. These data will also serve for the development of clinical trials involving homogeneous groups of patients.